PENGGUNAAN TEKNOLOGI TRADISIONAL BUBU PADA MASYARAKAT NELAYAN Di DESA OEMONGKONG KECAMATAN JEROWARU KABUPATEN LOMBOK TIMUR - Surya, Aidal Adi, AS (Multikultura, 2026)
This study examines a traditional maritime technology in the form of a fish trap known as bubu, which is used by fishing communities in Pemongkong Village, East Lombok, to catch blue swimming crabs (Portunus pelagicus). The focus of the discussion is on the design of the bubu and the methods of its use by local fishermen in Pemongkong Village. The research was conducted using a literature review method, with data sources derived from various written references and scientific publications. The results indicate that the use of bubu by these fishermen is more economically beneficial and environmentally friendly. Based on these findings, it can be concluded that the bubu has the potential to increase fishing productivity while posing no threat to the environment, making it highly suitable to be preserved and passed down from generation to generation as a traditional cultural practice among coastal communities in East Lombok.